PERANAN SEKOLAH DALAM PENDIDIKAN ISLAM - Ahmad Lahmi (Postgraduate Program Magister Pendidikan Agama Islam, 2016)
Education seems to still be the key words in building era of progress and civilization of mankind on this earth. Does not end there, that in Islam era means of space-time surrounding the creatures of the universe in this context the term that covers humans in any stages of social development of culture, politics, religion, system of valuesnorms are combined into one circle of civilization. Civilization itself drawn from the word 'adab (Islam) or civilization (Western) which means implies regularly, manners, discipline, respect, inclusive, caring, mutual help and so forth. Islamic education takes place in at least three neighborhoods that were interconnected, namely, home, community and school. Basically three educational environments are equally important because it contributes in giving, embed and develop the potential of the unique values and skills related to both affective and psychomotor. But today, the paradigm of education by the community has begun to shift by looking at formal educational institutions (schools) as a real education. This paper examines the role of school want to change the morals of learners in order to establish the Islamic civilization.